Implementasi Penguatan Usaha Mikro, Kecil dan Menengah (UMKM) melalui Program Food Photography di Baznas Kabupaten Jombang - M. Maulana Asegaf; Ferrary Alfa Ramadhan (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2022)
This research analyzes the implementation of strengthening UMKM (micro, small and medium businesses) at BAZNAS Jombang through the food photography program. Food Photography is one of the productive zakat programs that provide training mustahik who has businesses in the food sector. This program has good potential to support their promotion and distribution activities. This research uses a descriptive qualitative method and the data collection method was using an interview with the General Chair of BAZNAS Jombang, the economic program staff, and 13 mustahik of the Food Photography program. The results of this research show that the utilization of productive zakat through the Food Photography program of BAZNAS Jombang has been well implemented and runs optimally judging from the accuracy of the policy, accuracy of implementation, accuracy of targets, and the accuracy of the environment. The target of the Food Photography program is to improve marketing and branding skills for food products, increase promotion and distribution activities so that they can survive and thrive during the COVID-19 pandemic and be economically independent. Of the 13 mustahik, 10 of them have increased income, while the other 3 mustahik were stagnant, neither increased nor decreased. This shows that the Food Photography Workshop program at BAZNAS Jombang has a very positive impact on UMKM for the food sector, their income increases also can survive in the COVID-19 pandemic conditions and inspire enthusiasm in business to support the economy. There are inhibiting factors in its implementation, such as the limited human resources at BAZNAS Jombang which makes supervision not optimal.